The Influence of Debt To Equity Ratio, Net Profit Margin, and Cash Ratio on Firm Value - Renal Alvian; Agus Munandar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of Debt To Equity Ratio, Net Profit Margin, and Cash Ratio on firm value. Ratio data comes from the company's annual financial report (financial report), therefore the data collection method uses secondary data. This research was conducted from November 2021 to February 2022. Panel data were employed in this study, which is a synthesis of cross sectional and time series data. The normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test were all used in this study. The following conclusions are taken from the analysis and discussion of 45 samples from nine companies in the food and beverage subsector that are publicly traded on the Indonesian Stock Exchange: 1) The Debt To Equity Ratio has no effect on the firm's worth; 2) The Net Profit Margin has a positive and significant effect on the firm's worth; and 3) The Cash Ratio has a positive and significant effect on the firm's worth..